Implementation of 3D Animation-Based Learning Media to Increase Fantastic Makeup Creativity - Zahra Rifa Qanitah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Quality education can be created by educators who are able to adapt to the times so that they are able to create graduates who are in accordance with the needs of the community and are ready to compete in the international realm, including cosmetology education which has many competitors in the workforce. So, to be a professional fantasy makeup artist, you must have high creativity, unique and interesting to produce amazing fantasy makeup results. However, currently learning in makeup education on fantasy makeup material is still using conventional methods so that students feel bored and their creativity does not develop. For this reason, this research was conducted using descriptive quantitative methods with the aim of increasing student creativity to create makeup artists who can compete in the international realm. Based on the results of the study, it is known that the implementation of 3D animation-based learning media can increase the creativity of fantasy makeup because this method increases the impression received by students and also triggers them to have a stunning fantasy concept by combining one character with another character or with one character but has a uniqueness and its own character according to their respective makeup styles.